The application of biosecurity practices for preventing avian influenza in North-Eastern Italy turkey farms: An analysis of the point of view and perception of farmers - Stefania, Crovato; Alessio, Menini; Paolo, Mulatti; Tiziano, Dorotea; Favretto, Anna Rosa; Francesca, Zaltron; Giulia, Mascarello; Giandomenico, Pozza (Preventive veterinary medicine, 2024)
Italian and international outbreaks of highly pathogenic avian influenza (HPAI), particularly in densely populated poultry areas (DPPAs), have increased over the past few decades. These emerging risks, which endanger both human and animal health and the entire poultry industry, can be effectively limited by biosecurity measures implemented at human-animal food chain interfaces. Some problems, however, persist in the application of these measures on the part of poultry farmers, prompting the need to explore those aspects and causes that limit their implementation. A qualitative approach was selected for the study and a semi-structured interview technique was applied to collect data among turkey farmers (n = 29) working in the north-east of Italy. The aim of this technique was to gather data on farms in order to understand the biosecurity practices adopted and the reasons for and impediments to farmer implementation, or lack thereof. This article presents and discusses the main data collected. The study revealed that farmers were familiar with the biosecurity measures necessary to contain avian influenza (AI) and other poultry diseases; personal disinfection and animal isolation practices were particularly prominent. Based on the reported procedures, managerial, economic, and psychosocial factors were among the barriers behind the failure to implement biosecurity measures. These obstacles were variously intertwined and associated with the different action settings. In particular management factors, such as lack of time to apply the rules and difficulties contingent on the farm's structural characteristics, mediate the application of biosecurity measures. In terms of communication channels, the company, particularly its technicians, proved to be the primary source of information for farmers in case of emergencies, as well as the primary source of information on the application of biosecurity measures. However, other sources of information were indicated, such as word of mouth among farmers or other non-institutional figures (relatives and acquaintances). What emerged, was the need to improve not only the biosecurity management skills, but also to implement forms of cooperation among the various key stakeholders in the poultry sector. The information presented in this pilot study needs to be discussed among competent authorities, public and company veterinarians, company technicians, and farmers. Furthermore, this information will help in participatory co-planning of risk prevention and communication strategies to implement a long-term, sustainable, effective approach to address future epidemic emergencies.